TIME SERIES ANALYSIS OF LAND USE AND OCCUPATION IN PERMANENT PRESERVATION AREAS OF THE PARAÍBA RIVER BASIN - Tavares Silva, Madson; Nascimento de Sousa, Ayrton Flavio; Cunha França, Lorena Rayssa; Clemente de Lacerda, Mateus (Ra’e Ga: o Espaço Geográfico em Análise, 2023)
<span class="NormalTextRun SCXW260566771 BCX9" data-ccp-parastyle="resumo_raega" data-ccp-parastyle-defn=""ObjectId":"0ba6811d-5c85-4e48-a165-ce72741106e1|222","ClassId":1073872969,"Properties":[469775450,"resumo_raega",201340122,"2",134234082,"true",134233614,"true",469778129,"resumoraega",335572020,"1",201342446,"1",201342449,"1",469777841,"Calibri",469777842,"Times New Roman",469777843,"Times New Roman",469777844,"Calibri",201341986,"1",469769226,"Calibri,Times New Roman",268442635,"24",335551547,"1046",335559685,"567",335559737,"567",335551550,"6",335551620,"6",469777929,"resumo_raega Char",469778324,"Normal"]" data-ccp-parastyle-linked-defn=""ObjectId":"0ba6811d-5c85-4e48-a165-ce72741106e1|224","ClassId":1073872969,"Properties":[469775450,"resumo_raega Char",201340122,"1",134233614,"true",469778129,"resumoraegaChar",335572020,"1",134231262,"true",201342446,"1",201342449,"1",469777841,"Calibri",469777842,"Times New Roman",469777843,"Times New Roman",469777844,"Calibri",201341986,"1",469769226,"Calibri,Times New Roman",268442635,"24",335551547,"1046",469777929,"resumo_raega",469778324,"Default Paragraph Font"]">Any alteration caused in riparian areas of hydrographic basins directly causes changes in the dynamics of rivers, lakes, and urban areas with the elements of energy flow, dissolved material and sediments. Better planning, management and protection of natural resources in the areas of a river basin require knowledge of the characteristics of water courses, vegetation and land use and occupation. The present work aimed to analyze a time series of land use and occupation data in Permanent Preservation Areas (PPAs) of the Paraíba River Basin according to the precepts of the Brazilian Forest Code and with the aid of geoprocessing tools and the Pettitt test and Mann-Kendall test statistics. The Pettitt test showed a temporal change in the average natural cover starting in 2007, with an increase of 4.2%. Based on the Mann-Kendall test, there was a downward trend in the cover of riparian forests in 36.72% of the PPAs, prevailing over PPAs with upward trends, in the period from 1985 to 2006, demonstrating greater degradation of riparian forest areas during this period, mainly in the Middle and Lower Paraíba River regions. For the period from 2006 to 2020, there was a significant change in areas with upward trends in land with natural cover (28.31%), with an increase of 12.5% compared to the previous period.